Role of genetic in periodontal disease - Anand Narayanrao Wankhede; Sayli Anand Wankhede; Shilpa Prashant Wasu (Wolters Kluwer Medknow Publications, 2017)
Genetics is the study and understanding of the phenomena of heredity and variation. A large number of genes are associated with many systemic conditions. Periodontitis is inflammatory condition of periodontium. Periodontium consists of gingiva, periodontal ligament, cementum, and alveolar bone. It is considered being a multifactorial disease. Studies of animals and humans support the concept that a large number of genes' factor may be associated with periodontitis and clearly play a role in the predisposition and progression of periodontal diseases. It has been proven that genetic factors impair inflammatory and immune responses during periodontal diseases. Research on identifying specific genes causing periodontitis may improve and prevent the disease progression. The aim of this article is to focus on genetic risk factors and its influence for the various forms of periodontal disease.